NLR-protein functions in immunity (2015)
The Nod-like receptor (NLR) family of proteins are evolutionary conserved molecules that in plants and mammals have been implicated in innate immune sensing of microbes and infection-associated physiological changes, contributing to immune protection of the challenged host organism through the instruction of inflammatory responses, antimicrobial defense and adaptive immunity. Recent data however suggests that the biological roles of NLR go beyond the function of classical pattern recognition molecules (PRM) as they have been implicated in essential cellular processes including autophagy, apoptosis, modification of signal transduction and gene transcription as well as reproductive biology. In this research topic, we aim to provide a comprehensive state-of the art overview of the emerging functions of NLR in plant and mammalian immunity, cell biology and reproductive biology. Potential topics may include, but are not limited to the following areas: • Functions of NLRs as PRMs in infection • Cross-talk of NLRs with other PRMs • Signal transduction pathways of NLRs • New functions of NLRs other than pattern recognition • Structural aspects of NLR activation • Mechanisms of NLRs in cell biological processes • Aspects of NLRs in reproductive biology • Functions of NLRs in plant immune responses